Images of the "other": Pan American Airways, Americanism, and the idea of Latin America. (December 2017) - Mercer, Danielle; Paludi, Mariana I; Mills, Albert J; Mills, Jean Helms
This article explores the relationship between Pan American World Airways (Pan Am) and Latin America to understand the role of Western multinational corporations in the historical processes of postcoloniality—that is, the representation of the non-Western "other" to Western audiences. Informed by postcoloniality and the use of a critical hermeneutics method, we draw on 64 years of archived materials from the Pan American World Airways Collection 341, housed at the Otto Richter Library at the University of Miami, as well as numerous histories of the airline. Our findings show how Pan Am gained a powerful position, both politically and economically, which facilitated its ability to construct influential images of Latin American employees, citizens, and the idea of Latin America. Although Pan Am ceased operations in 1991, its years of dominance in South America had the capability to contribute and provide insights into our understanding of the continued postcolonial processes and the idea of (North) "Americanism." More importantly, our article demonstrates how using a postcolonial framework can assist organizational and business scholars to better understand the role that historical patterns play in organizations still today. We hope that using alternative methodologies and theories such as postcolonialism to examine contemporary management culture, we will better be able to understand how history has been "written" in an effort to lessen "Western" ideologies and include diverse epistemological perspectives.